2000
DOI: 10.1046/j.1440-1681.2000.03349.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal And Cardiovascular Actions Of 20‐Hydroxyeicosatetraenoic Acid And Epoxyeicosatrienoic Acids

Abstract: 4. In summary, the available evidence indicates that CYP metabolites of AA play a central role in the regulation of renal, pulmonary and vascular function and that abnormalities in this system may contribute to the pathogenesis of cardiovascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
97
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(97 citation statements)
references
References 112 publications
(271 reference statements)
0
97
0
Order By: Relevance
“…For example, EETs have potent vasodilatory properties [37] and 20-hydroxyeicosatetraenoic acid (20-HETE) has potent vasoconstrictive effects [38]. Therefore, changes in the expression and/or activity of specific CYP epoxygenase and hydroxylase enzymes can alter the delicate balance between EETs and 20-HETE.…”
Section: Arachidonic Acid Cyp Epoxygenases and Soluble Epoxide Hydromentioning
confidence: 99%
See 2 more Smart Citations
“…For example, EETs have potent vasodilatory properties [37] and 20-hydroxyeicosatetraenoic acid (20-HETE) has potent vasoconstrictive effects [38]. Therefore, changes in the expression and/or activity of specific CYP epoxygenase and hydroxylase enzymes can alter the delicate balance between EETs and 20-HETE.…”
Section: Arachidonic Acid Cyp Epoxygenases and Soluble Epoxide Hydromentioning
confidence: 99%
“…K Ca channels can be activated by elevations in intracellular Ca 2+ and membrane depolarization [65,66]. CYP epoxygenase derived EETs are known activators of BK Ca channels in vascular smooth muscle [20,67], whereas, CYP ω-hydroxylases derived HETEs are known inhibitors in vascular smooth muscle [38,68,69]. Recent evidence suggests that newly identified K Ca channels in cardiac mitochondria (mito K Ca ) [53,70] are important mediators of cardioprotection.…”
Section: K + Channels and Cardioprotectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of the synthesis of 20-HETE attenuates the vasoconstrictor response of renal arterioles to elevations in transmural pressure in vitro (16, 18) and autoregulation of renal blood flow and tubuloglomerular feedback responses in vivo (8,48). At the level of the renal tubules, 20-HETE inhibits sodium reabsorption in the proximal tubule and thick ascending limb of the loop of Henle (6,32,34,39).Previous studies indicated that the renal production of EETs and/or 20-HETE is altered in diabetes and in genetic and experimental models of hypertension (1,7,21,24,25,28,41). The release of 20-HETE in renal and peripheral blood vessels is stimulated by ANG II (5), phenylephrine (20a), endothelin (37), and serotonin (3).…”
mentioning
confidence: 99%
“…Previous studies indicated that the renal production of EETs and/or 20-HETE is altered in diabetes and in genetic and experimental models of hypertension (1,7,21,24,25,28,41). The release of 20-HETE in renal and peripheral blood vessels is stimulated by ANG II (5), phenylephrine (20a), endothelin (37), and serotonin (3).…”
mentioning
confidence: 99%